Implementasi Sistem Kalkulasi Berat Dan Iuran Sampah Berbasis Internet Of Things Pada Perumahan Bekasi Jaya Indah - Abdu Aziz Muttaqin; Ahmad Chusyairi (Fakultas Sains Dan Teknologi Universitas Islam Asyafiiyah, 2024)
Waste is a complex problem in developing countries like Indonesia, negatively impacting the environment and public health. Bekasi Jaya Indah Housing Estate, Bekasi City, faces the challenge of sub-optimal waste management. One of them is the gap between waste fees and the weight of waste generated, especially from houses with home industry activities. This research aims to improve monitoring efficiency by developing a tool based on firebase technology or user interface. This technology allows real-time access from various locations to monitor environmental conditions. This tool is not only a monitor of environmental conditions, but also a management tool to support better decision making in maintaining environmental stability and safety. The method used is the prototype method with the stages of communication, quick plan, quick design modeling, construction of prototype, and deployment delivery & feedback. This monitoring tool, it is expected that residents, officers, and administrators can easily monitor environmental conditions from various locations. User have the ability to take the necessary response actions quickly based on real-time information obtained from this monitoring tool.